Dampak Waralaba pada Kawasan Permukiman Bidang Penelitian dan Pengembangan di BAPPEDA - Fauziah Septiani; Nurmin Arianto (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
A franchise business cannot be separated from meeting the economic needs of business owners and increasing living standards. The mindset of businesspeople is always profitable as long as the business can run and relies heavily on business instincts in running a business. This study measures the impact of the existence of franchises in residential areas on the economy of the people of Tangerang district with a qualitative method with a phenomenology approach using content analysis and SWOT analysis methods. Qualitative findings indicate that the pattern of services provided by franchises is perceived to be better than the services of traditional traders. Therefore, the Regional Government of Tangerang Regency must take a joint role with traditional market managers in improving traditional markets and setting minimum service standards as well as capacity building and community empowerment in the economic sector, business development, providing Job Training Center (BLK) facilities that can be a place for coaching traditional traders.